Ties that bind : the story of an Afro-Cherokee family in slavery and freedom - Miles, Tiya, 1970- (American crossroads ;, 2015)
"This beautifully written book tells the haunting saga of a quintessentially American family. It is the story of Shoe Boots, a famed Cherokee warrior and successful farmer, and Doll, an African slave he acquired in the late 1790s. Over the next thirty years, Shoe Boots and Doll lived together as master and slave and also as lifelong partners who, with their children and grandchildren, experienced key events in American history--including slavery, the Creek War, the founding of the Cherokee Nation and subsequent removal of Native Americans along the Trail of Tears, and the Civil War. This is the gripping story of their lives, in slavery and in freedom"--Provided by publisher